1994
DOI: 10.1016/0304-4017(94)90073-6
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic resistance in goats in peninsular Malaysia

Abstract: Ninety-six randomly selected farms, located throughout peninsular Malaysia, were surveyed for goat nematodes resistant to benzimidazoles (BZ). On 33 farms BZ resistance was demonstrated by means of an egg hatch assay. Haemonchus contortus was found to be the main species involved in anthelmintic resistance. There was a positive association between the frequency of anthelmintic treatments on a farm and the presence of benzimidazole resistance. To assess the value of the egg hatch assay, faecal egg count reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 29 publications
1
32
0
5
Order By: Relevance
“…The reduction in the anthelmintic treatment will be feasible by keeping in mind the local epidemiology of trichostrongylosis and if some additional pasture management strategies are also developed (Coles and Roush 1992). Egg hatch assay was used to confirm the results of FECRT, which indicated development of resistance in gastrointestinal nematodes against OXF on all farms, in contrast to Martin et al (1989) and Dorny et al (1994).…”
Section: Discussionmentioning
confidence: 95%
“…The reduction in the anthelmintic treatment will be feasible by keeping in mind the local epidemiology of trichostrongylosis and if some additional pasture management strategies are also developed (Coles and Roush 1992). Egg hatch assay was used to confirm the results of FECRT, which indicated development of resistance in gastrointestinal nematodes against OXF on all farms, in contrast to Martin et al (1989) and Dorny et al (1994).…”
Section: Discussionmentioning
confidence: 95%
“…There is also strong evidence that resistance develops more rapidly in regions where animals are dewormed regularly. Serious problems with AR in Haemonchus contortus were reported in some humid tropical areas where 10 to 15 treatments per year were used to control this parasite in small ruminants (42).…”
Section: Contributing Factors For the Development Of Resistancementioning
confidence: 99%
“…This in vitro test has the advantage of requiring only one fecal sample. However, several authors have reported poor correlations between the results of the FECRT and the egg hatch test for helminths of livestock (14,42).…”
Section: Detection Of Drug Resistancementioning
confidence: 99%
“…The main factor evoked to select for resistance concerns treatment frequency and, "a large number of anthelmintic treatments with the same anthelmintic family for years" is taken as the key factor for selecting for resistance [91]. This statement is supported by surveys realised on a regional scale, in New Zealand [59,83]; in Malaysia [33]; in South Africa [95]; in the United Kingdom [53,75]; in Australia [36,72]. The "same" repeated anthelmintic treatment is a major cause, in experimental and oversimplified conditions (three-month-old lambs, synchronous infestation with only one to three gastro-intestinal nematode species...) of positive correlation between intensity of resistance and treatment frequency [5,66,71].…”
Section: Introductionmentioning
confidence: 99%